To what extent does manager’s leadership style influence hotel front liners to become customer-oriented? A study in Malaysian small and medium sized budget hotels - Mohd Noor, Nor Azila; Chowdhury, Mohammed Shamsul; Jamaludin, Siti Noratisah; Muhammad, Azli; Abdul Rahman, Maria (International digital organization for scientific information (IDOSI), 2011)
This research seeks to examine a relationship between manager's leadership style and customer orientation behavior of the front line employees. Customer-orientation behavior has been defined as the employee's tendency or predisposition to meet client's need in the job context and has become a prime variable of interest for organizations wishmg to market and promote products to the customers.In hotel industry in particular, one way to improve the quality of services offered is through the prompt and courteous service quality given by the front liners, that is by adopting customer-orientation behaviour.Despite of its importance of customer-orientation to the service organizatiom, a complete understanding of the process and its antecedents is presently lacking. To acheve the purposes of the study, data were collected from front line employees in small and medum sized budget hotels in Malaysia.Using a swey method, thls study explores the influence of leadership styles on customer-orientation behaviour of the front liners.Hypothesized relationships are tested using swey responses from a sample of 142 hotel front liners in Malaysia. Results are compared with earlier findngs and implicatiom for future research are dscussed.